2020
DOI: 10.1126/sciadv.aaz0404
|View full text |Cite
|
Sign up to set email alerts
|

A multifunctional surfactant catalyst inspired by hydrolases

Abstract: The remarkable power of enzymes to undertake catalysis frequently stems from their grouping of multiple, complementary chemical units within close proximity around the enzyme active site. Motivated by this, we report here a bioinspired surfactant catalyst that incorporates a variety of chemical functionalities common to hydrolytic enzymes. The textbook hydrolase active site, the catalytic triad, is modeled by positioning the three groups of the triad (-OH, -imidazole, and -CO2H) on a single, trifunctional surf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
30
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 48 publications
(30 citation statements)
references
References 73 publications
(91 reference statements)
0
30
0
Order By: Relevance
“…Synthetic esterases are one of the most studied enzyme-mimicking cataysts. , Recent examples, built on peptide or purely abiotic scaffolds, commonly contain either a Lewis acidic metal ion such as zinc to activate water , or a catalytic triad to mimic those found in serine proteases. Although these studies used different reaction conditions, the catalytic efficiency of MINP­( 1 + 5e ) ( k cat / K m = 343 M –1 s –1 at pH 7, 25 °C) compared favorably with those of previously reported systems for PNPA hydrolysis ( k cat / K m = 2–100 M –1 s –1 at pH 6.2–8.0, 22–25 °C), and was close to that (450 M –1 s –1 ) of a synthetic esterase (formed from amyloid fibrils) at pH 8, 38 °C, under high pressure (200 MPa) . The catalytic turnover number (TON) of MINP­( 1 + 5e ) was >510 (Figure b), also significantly higher than those in the literature (mostly >10–20). …”
mentioning
confidence: 73%
“…Synthetic esterases are one of the most studied enzyme-mimicking cataysts. , Recent examples, built on peptide or purely abiotic scaffolds, commonly contain either a Lewis acidic metal ion such as zinc to activate water , or a catalytic triad to mimic those found in serine proteases. Although these studies used different reaction conditions, the catalytic efficiency of MINP­( 1 + 5e ) ( k cat / K m = 343 M –1 s –1 at pH 7, 25 °C) compared favorably with those of previously reported systems for PNPA hydrolysis ( k cat / K m = 2–100 M –1 s –1 at pH 6.2–8.0, 22–25 °C), and was close to that (450 M –1 s –1 ) of a synthetic esterase (formed from amyloid fibrils) at pH 8, 38 °C, under high pressure (200 MPa) . The catalytic turnover number (TON) of MINP­( 1 + 5e ) was >510 (Figure b), also significantly higher than those in the literature (mostly >10–20). …”
mentioning
confidence: 73%
“…It has been shown that catalytic triads from serine proteases (H, S, and D residues) that have been incorporated in a designed lipopeptide-like molecule lead to an effective hydrolase. 197 The peptide surfactant coassembles with conventional cationic surfactants into spherical micelles. Other researchers have explored the use of peptides as agents to bind and template nanoparticles such as gold and silver nanoparticles with a diversity of catalytic properties.…”
Section: Peptide Catalysts With Metal Nanoparticlesmentioning
confidence: 99%
“…It has been shown that catalytic triads from serine proteases (H, S, and D residues) that have been incorporated in a designed lipopeptide-like molecule lead to an effective hydrolase . The peptide surfactant coassembles with conventional cationic surfactants into spherical micelles.…”
Section: Peptide Catalysts With Metal Nanoparticlesmentioning
confidence: 99%
“…Further, recent design of minimal peptide based soft nanostructures has been exploited to mimic the advanced function of evolved hydrolytic enzymes. [75][76][77][78][79][80][81][82][83][84][85][86][87][88][89][90][91] In this regard, Stupp and co-workers have designed a peptide amphiphile (histidine groups linked with the N-terminal of KLLLAAA-palmitoyl) with exposed histidine groups that selfassembled to form fibrillar nanostructures which showed excellent hydrolytic activity of the model substrate 2,4-dinitrophenyl acetate. The work highlighted that supramolecular assemblies could expose catalytic residues towards the solvent to feature esterase like activity.…”
Section: Peptide Assemblies For Diverse Enzymatic Transformationsmentioning
confidence: 99%